Mechanical response design of arch seat foundation under complex traffic loading - Dong Xia; Guanguo Liu; Dingxin Zhang; Tong Luo (PLoS ONE, 2025)
The mechanical response of the arch seat foundation of extra-long-span arch bridges under complex traffic loads has not been fully understood. To address this gap, this study develops a field-scale three-dimensional finite element model (3D FEM) of the arch seat foundation based on a large- span arch bridge project in China. Accounting for complex traffic loads-including longitudinal and transverse temperature gradients, braking forces, and wind loads-a detailed analysis was performed on the stress distribution of the foundation, load transfer of vertical and slanted piles, and stress-strain behaviors of the surrounding rock. The results show that the maximum tensile stress in the foundation is localized in the connection zone between the arch abutment cap and the arch springing. Tensile forces are most pronounced at the top of vertical piles, while the maximum bending moment occurs at the pile heads. Furthermore, plastic strain and settlement of the soil-rock mass are concentrated in the interconnected regions among the arch springing, cap, and main beam. Thus, it is critical to optimize reinforcement design at these key locations, implement long-term stress and strain monitoring, and mitigate the initiation and fatigue propagation of microcracks.